Impact of Technological Interventions on Human Resource Practices and Organizational Effectiveness: An Empirical Study (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Human Resource Management (HRM) has moved far beyond its traditional administrative role and now functions as a strategic driver of organizational effectiveness. In recent years, rapid advances in information and digital technologies have fundamentally reshaped HR practices through the adoption of Human Resource Information Systems (HRIS), e-HRM platforms, automation tools, and analytics-driven decision-making. These technological interventions have transformed core HR functions such as recruitment, selection, training, performance appraisal, compensation, and employee engagement. The present study empirically examines the influence of technological interventions in HR practices on HR efficiency and organizational effectiveness in selected IT firms operating in Bengaluru. Primary data were collected from 300 respondents using a structured questionnaire. The data were analyzed using descriptive statistics, factor analysis, ANOVA, and multiple regression techniques. The findings reveal a statistically significant and positive relationship between technology-enabled HR practices and HR efficiency, indicating that digital HR systems contribute meaningfully to improved employee satisfaction, operational efficiency, and strategic alignment. The study highlights the growing importance of integrating technology with HR strategy to achieve sustainable organizational performance.